Emotional intelligence as a moderator in the emotional labour - burnout relationship: evidence from Malaysian HR professionals. (2016) - Mustafa, Michael; Santos, Angeli; Chern, Gwi Terk
The role of emotions amongst employees with extensive interpersonal interactions has been identified as critical for both individual and organisational performance. This particular study examines the relationship between emotional labour, trait emotional intelligence and three dimensions of burnout. Specifically, we examine whether trait emotional intelligence moderates the relationship between emotional labour and burnout. Based on a sample of 136 Malaysian HR professionals, we find that surface acting, but not deep acting, is a significant direct predictor of personal and work-related burnout. More interestingly though, trait emotional intelligence only buffered the effects between deep acting strategies and personal and work-related burnout. The findings from our study contribute to a deeper understanding of the conditions under which emotional labour can be beneficial to employee well-being.